Partnership Model in Supporting Principal Performance - Mayasari, Mayasari; Ahmad, Suriansyah; Purwanti, Ratna (Journal of English Language and Education, 2025)
Continuous cooperation in a partnership must always include effective and open communication so that stakeholders understand and know the performance system of the institution that is entrusted in developing a directed and effective education for children and education. This research is to find out the management and utilization of existing resources, both teacher resources and infrastructure resources managed by schools in cooperation and collaboration with stakeholders and partnerships that always support every decision making in helping the development of human resources (teachers) and school infrastructure. The collaboration built by parents and school management has a great impact both on the success of an educational institution and on teacher resources and school infrastructure in addition to facilitating schools for student growth by carrying out sustainable collaboration. In order to create good cooperation between schools and the community, the community needs to know and have a clear picture of the school concerned.   The description and condition of the school can be informed to the public through reports to parents of students.